Annual Plan 2001-2002 - Planning Commission (Planning Commission, 2001)
Coconut is the major crop of the territory and agriculture the productive sector of the islands economy. The entire cultivable area in the territory is under coconut and there is no scope for further expansion of area of crop. The production level by the end of VIII Five Year Plan will be at 27.5 million nuts per year. At the beginning of the VIII Five Year Plan the level of production were about 25.0 million nuts per year. The IX Five Year Plan give adequate thrust for increasing production and productivity of coconut. The end of the Five Year Plan targets the level of production targeted at 30 million nuts and also the oil content by adding one per cent of the present level. The package approach for increasing production and productivity are amply discussed under the relevant schemes.
Administration of the Onion Territory of Lakshadweep
Administration of the Onion Territory of Lakshadweep